Pengaruh Kompetensi SDM, Sistem Pengendalian Internal dan Penggunaan SISKUDES Terhadap Akuntabilitas Dana Desa - Rahul Khan; Heni Yulsiati; Siska Aprianti (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of Human Resource Competence, Government Internal Control System (SPIP), and the use of the Village Financial System (Siskeudes) on the accountability of village fund management in Pulau Rimau District, Banyuasin Regency. Method: This research employs a quantitative approach with descriptive and associative methods. Primary data are collected through questionnaires distributed to village officials directly involved in village financial management. The population consists of 85 village officials from 17 villages in Pulau Rimau District, and all population members are used as the sample through a saturated sampling (census) technique. Data are analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS software. Finding: The study is expected to demonstrate that Human Resource Competence, Government Internal Control System (SPIP), and the use of Siskeudes have a positive and significant effect on the accountability of village fund management, both partially and simultaneously. Improved competence of village officials, effective internal control, and optimal utilization of Siskeudes are expected to enhance transparency, accuracy, and accountability in village financial management. Novelty: This study contributes to the literature by examining the influence of Human Resource Competence, SPIP, and Siskeudes on village fund management accountability in Pulau Rimau District, an area that has received limited research attention. Furthermore, this study incorporates the latest regulatory framework, namely Law Number 3 of 2024 concerning Villages, which has not been widely adopted in previous studies.